PROTECTION OF THE WOLF IN THE INTERNATIONAL AND EUROPEAN UNION LEGAL SYSTEMS - Sobieraj, Kamila; Zacharczuk, Piotr (Review of European and Comparative Law, 2020)
This publication attempts to present comprehensively the principal legal acts that oblige the EU and all its Member States to secure favourable conservation sta-tus of the wolf population, as well as international legal acts regarding that issue . It also emphasizes the obligation to protect the ecological continuity between the places these carnivores inhabit . It should be pointed out that the existing publica-tions on the EU and international wolf protection regulations are limited to the two undoubtedly most important acts: the Bern Convention and the Habitats Directive .